2007
DOI: 10.1016/j.envpol.2007.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Is an adjusted rhizosphere-based method valid for field assessment of metal phytoavailability? Application to non-contaminated soils

Abstract: An adjusted-RHIZO method was the most promising approach for predicting metal phytoavailability to wheat under field conditions. AbstractPreviously recommended rhizosphere-based method (RHIZO) applied to moist rhizosphere soils was integrated with moist bulk soils, and termed adjusted-RHIZO method (A-RHIZO). The A-RHIZO and RHIZO methods were systematically compared with EDTA, DTPA, CaCl 2 and the first step of the Community Bureau of Reference (BCR1) methods for assessing metal phytoavailability under field c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 34 publications
4
21
1
Order By: Relevance
“…Feng et al (2005a, b), in two studies comparing the suitability of LMWOAs and other extractants to predict heavy metal uptake by wheat and barley from rhizosphere soils, also found this extractant to be the best estimator for Cu and Zn (but not for Ni) considering all the soils but also dividing them as function of pH. The ability of this extractant to estimate Cu, Zn and also Ni uptake was proved by Shan et al (2003), Wang et al (2003) and Fang et al (2007). Finally, Vázquez et al (2008) found LMWOAs the best estimator of Cu and Zn uptake by white lupin grown in nine acid-polluted soils.…”
Section: Cu Rootmentioning
confidence: 81%
“…Feng et al (2005a, b), in two studies comparing the suitability of LMWOAs and other extractants to predict heavy metal uptake by wheat and barley from rhizosphere soils, also found this extractant to be the best estimator for Cu and Zn (but not for Ni) considering all the soils but also dividing them as function of pH. The ability of this extractant to estimate Cu, Zn and also Ni uptake was proved by Shan et al (2003), Wang et al (2003) and Fang et al (2007). Finally, Vázquez et al (2008) found LMWOAs the best estimator of Cu and Zn uptake by white lupin grown in nine acid-polluted soils.…”
Section: Cu Rootmentioning
confidence: 81%
“…Single extraction procedures are based on the assumption that there is a relationship between the extractable fraction of soil heavy metals and the availability of heavy metals to plants; that is to say, a good correlation indicates that a certain fraction of the total metal is available to plants (Fang et al 2007). Our results indicate that the NH 4 OAc-extractable fraction in moist soil may provide a method to estimate the availability of Zn and Cd to S. plumbizincicola on the basis of linear correlation coefficients.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the nature of the reactant used, they fall into three categories (Lebourg et al, 1996;Sutherland, 2002). Firstly, those which employ salts as CaCl 2 or Ca(NO 3 ) 2 (e.g., An and Kampbell, 2003;Fang et al, 2007), in order to leach cations adsorbed onto solid materials, due to permanent structural charges (phyllosilicates, phyllomanganates and sometimes organic matter). Secondly, techniques which employ acid solutions, in order to simulate the effect of an acid input (e.g.…”
Section: Introductionmentioning
confidence: 99%